Intussusception and appendicitis: What comes first? - Raffaella Cocomazzi; Alessia Salatto; Vittoria Campanella; Cosetta Maggipinto; Francesco Canale; Flavia Indrio; Maria Nobili; Fabio Bartoli (Elsevier, 2021)
Intussusception and acute appendicitis are two different causes of acute abdomen that potentially require surgery. The clinical presentation can be similar in both diagnoses with symptoms including abdominal pain, vomiting, diarrhea, and fussiness but these two concern a pediatric population of different ages. We describe an uncommon CASE combining appendicular intussusception with concurrent acute appendicitis. A 27-month-old boy presented with 3 day of colicky intermittent abdominal pain, non-bilious vomit and low-grade fever. After the failure of air enema decompression, the child underwent a surgical procedure.